Leaf chlorophyll content in North Sulawesi (Indonesia) local rice cultivars subjected to polyethylene glycol (PEG) 8000-induced water deficit at the vegetative phase (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Nio SA, Pirade M, Ludong DPM. 2019. Leaf chlorophyll content in North Sulawesi (Indonesia) local rice cultivars subjected to polyethylene glycol (PEG) 8000-induced water deficit at the vegetative phase. Biodiversitas 20: 2462-2467. Climate change can result in drought stress in the environment and this condition reduces rice production. Polyethylene glycol (PEG) is used to induce water deficit, because it is able to decrease water potential in the solution. The present study aimed to evaluate the physiological response of North Sulawesi local rice (cvs. Superwin, Ombong, Burungan, and Temo) to PEG 8000-induced water deficit based on the leaf chlorophylls (a, b and total chl.) content at the vegetative phase. The results of this study showed that PEG 8000-induced water deficit with media water potential (WP) -0.25 and -0.5 MPa decreased the content of leaf total chlorophyll and leaf chlorophyll a. The longer treatment period could reduce the contents of leaf total chlorophyll, chlorophyll a and chlorophyll b. The content of leaf chlorophyll total and chlorophyll a were potential physiological indicators for North Sulawesi local rice response to PEG 8000-induced water deficit.
Keywords: Chlorophyll, drought, North Sulawesi local rice, vegetative